Biomedicine, self and society: An agenda for collaboration and engagement [version 1; referees: 2 approved] - Martyn Pickersgill; Sarah Chan; Gill Haddow; Graeme Laurie; Devi Sridhar; Steve Sturdy; Sarah Cunningham-Burley (Wellcome Open Research, 2019)
The commitment of massive resources – financial, social, organisational, and human – drives developments in biomedicine. Fundamental transformations in the generation and application of knowledge are challenging our understandings and experiences of health, illness, and disease as well as the organisation of research and care. Coupled with the accelerated pace of change, it is pressing that we build authentic collaborations across and between the biomedical sciences, humanities and social sciences, and wider society. It is only in this way that we can ask and answer the penetrating questions that will shape improvements in human health now and in the decades ahead. We delineate the need for such commitments across five key areas of human and societal experience that impact on and are impacted by developments in biomedicine: disease; bodies; global movements and institutions; law; and, science-society engagements. Interactions between ideas, researchers, and communities across and within these domains can provide a way into creating the new knowledges, methods, and partnerships we believe are essential if the promises of biomedicine are to be realised.